Low Power CMOS Electrocardiogram Amplifier Design for Wearable Cardiac Screening - Ow Tze Weng; Suhaila Isaak; Yusmeeraz Yusof (Institute of Advanced Engineering and Science, 2018)
The trend of health care screening devices in the world is increasingly towards the favor of portability and wearability. This is because these wearable screening devices are not restricting the patient’s freedom and daily activities. While the demand of low power and low cost biomedical system on chip is increasing in exponential way, the front-end electrocardiogram (ECG) amplifiers are still suffering from flicker noise for low frequency cardiac signal acquisition, 50Hz power line electromagnetic interference, and the large unstable input offsets due to the electrode-skin interface is not attached properly. In this paper, a CMOS based ECG amplifier that suitable for low power wearable cardiac screening is proposed. The amplifier adopts the highly stable folded cascode topology and later being implemented into RC feedback circuit for low frequency DC offset cancellation. By using 0.13µm CMOS technology from Silterra, the simulation results show that this front-end circuit can achieve a very low input referred noise of 1pV/Hz1/2 and high common mode rejection ratio of 174.05dB. It also gives voltage gain of 75.45dB with good power supply rejection ratio of 92.12dB. The total power consumption is only 3µW and thus suitable to be implemented with further signal processing and classification back end for low power wearable biomedical device.